Senecjańskie „noli me tangere" - Wesołowska, Elżbieta (Przestrzenie Teorii, 2007)
The paper concerns the question (deals with the question) of the role of proximity in Seneca's tragedies. The title expression "noli me tangere", although not originally Senecan, is given a symbolic nature being quite convenient to eulcidate the peculiar interpersonal distance in Roman tragedies. Avoidance of the physical contact has its roots in the stoical doctrine based on fear of the emotions especially arisen in the mutual human relations. However, it also seems to be obvious that in such a construction of dramatic interaction there is some evidence both of the author's own nature and of his difficult social situation (as an exile on Corsica or during his "inner emigration" toward the end of his life). It is worth mentioning that the "frozen" situation between Seneca's dramatis personae is paradoxically a factor of a rising dramatic effect.